SINTESIS BAHAN M-HEXAFERRITES DENGAN DOPING LOGAM Co MENGGUNAKAN METODE KOPRESIPITASI - Khaerunnisa Khaerunnisa; Susilawati Susilawati; Lalu Rudyat Telly Savalas; Muhammad Taufik; Wahyudi Wahyudi (Postgraduate, University of Mataram, 2018)
Has successfully carried out the synthesis of M-hexferrites with doping metal Co. using coprecipitation method in which the basic material used in this study is BaCO3, FeCl3.6H2O, and CoCl2 (Pa) in the form of powder with a purity of 99.99% by mole fraction 0, 0 , 2, 0.5, 0.8 and 1. BaCO3 dissolved in HCl with 0.1 N. The process of dissolving BaCO3 using a hot plate and stirred using a magnetic stirrer until the temperature reaches 70°C for 2 hours, to prepare a solution and dissolve Iron CoCl2.6H2O (III) Chloride Hexahydrate FeCl3.6H2O, then a third mixing a solution of BaCO3, CoCl2.6H2O and Iron (III) Chloride Hexahydrate FeCl3.6H2O it in a beaker and stirred using a magnetic stirrer to form a homogeneous solution (brownish black color) and then adding a solution NH4OH precipitating the burette so that the precipitate obtained with high homogeneity. The samples were cooled and washed with distilled water, filtered with filter paper until pH neutral (pH = 7), the material is dried precipitated by using an oven temperature of 80°C. Furthermore, the process of grinding in order to obtain a brownish powder and calcined at varying temperatures of 400, 600 and 800ºC for 4 hours.Keywords: Barium M-heksaferit, cobalt, coprecipitation